Учебная практика по развитию цифровых компетенций (13.03.02): электронный курс - Колчанова В. А. Вероника Андреевна; Шандарова Е. Б. Елена Борисовна; Козлова Л. Е. Людмила Евгеньевна; Сыса Е. А. Елена Александровна (Томск, TPU Moodle, 2022)
Заглавие с экрана